2022
DOI: 10.1111/cts.13297
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone exposure in normal‐weight and obese hospitalized COVID‐19 patients: An observational exploratory trial

Abstract: During the latest pandemic, the RECOVERY study showed the benefits of dexamethasone (DEX) use in COVID-19 patients. Obesity has been proven to be an independent risk factor for severe forms of infection, but little information is available in the literature regarding DEX dose adjustment according to body weight.We conducted a prospective, observational, exploratory study at Geneva University Hospitals to assess the impact of weight on DEX pharmacokinetics (PK) in normalweight versus obese COVID-19 hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…DEX once a day at an oral dose of 6 mg for up to 10 days is a recommended dosing regimen for treatment of COVID-19 patients requiring mechanical ventilation. A clinical trial found mean concentrations achieved in the blood of COVID-19 patients upon single oral administration of DEX at a dose of 6 mg were far above IC 50 values of inhibition of TNFα, IL-6, and NO production estimated in this study (Abouir et al, 2022). In that clinical trial, the mean blood concentration of DEX at 8 h was around 74 29 ng•mL -1 in normal-weight patients.…”
Section: Discussionmentioning
confidence: 40%
“…DEX once a day at an oral dose of 6 mg for up to 10 days is a recommended dosing regimen for treatment of COVID-19 patients requiring mechanical ventilation. A clinical trial found mean concentrations achieved in the blood of COVID-19 patients upon single oral administration of DEX at a dose of 6 mg were far above IC 50 values of inhibition of TNFα, IL-6, and NO production estimated in this study (Abouir et al, 2022). In that clinical trial, the mean blood concentration of DEX at 8 h was around 74 29 ng•mL -1 in normal-weight patients.…”
Section: Discussionmentioning
confidence: 40%
“…The metabolism of DEX is through CYP3A4‐mediated hydroxylation 21 . The pro‐inflammatory cytokines, including IL‐6 and TNFα strongly decrease mRNA expression and enzyme activity of CYP enzymes including CYP3A4 in human hepatocytes 22,23,38 . However, our simulations (Figure 4) show no substantial risk of DEX accumulation, even at the highest dose of 12 mg daily for 10 days.…”
Section: Discussionmentioning
confidence: 79%
“…The PKs of DEX among hospitalized patients with COVID‐19 was assessed without evaluation of potential influences of covariates, such as weight or sex or disease severity. The source publication lacked this information for individual patients 23 . However, our approach was sufficient to allow simulations of DEX concentration‐time profiles in patients with COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations